Mitochondrial polymerase gamma dysfunction and aging cause cardiac nuclear DNA methylation changes - Koczor, Christopher A. (Physiol Genomics, 2016)
Cardiomyopathy (CM) is an intrinsic weakening of myocardium with contractile dysfunction and congestive heart failure (CHF). CHF has been postulated to result from decreased mitochondrial energy production and oxidative stress. Effects of decreased mitochondrial oxygen consumption also can accelerate with aging. We previously showed DNA methylation changes in human hearts with CM. This was associated with mitochondrial DNA depletion, being another molecular marker of CM. We examined the relationship between mitochondrial dysfunction and cardiac epigenetic DNA methylation changes in both young and old mice. We used genetically engineered C57Bl/6 mice transgenic for a cardiac-specific mutant of the mitochondrial polymerase-γ (termed Y955C). Y955C mice undergo left ventricular hypertrophy (LVH) at a young age (∼94 days old), and LVH decompensated to CHF at old age (∼255 days old). Results found 95 genes differentially expressed as a result of Y955C expression, while 4,452 genes were differentially expressed as a result of aging hearts. Moreover, cardiac DNA methylation patterns differed between Y955C (4,506 peaks with 68.5% hypomethylation) and aged hearts (73,286 peaks with 80.2% hypomethylated). Correlatively, of the 95 Y955C-dependent differentially expressed genes, 30 genes (31.6%) also displayed differential DNA methylation; in the 4,452 age-dependent differentially expressed genes, 342 genes (7.7%) displayed associated DNA methylation changes. Both Y955C and aging demonstrated significant enrichment of CACGTG-associated E-box motifs in differentially methylated regions. Cardiac mitochondrial polymerase dysfunction alters nuclear DNA methylation. Furthermore, aging causes a robust change in cardiac DNA methylation that is partially associated with mitochondrial polymerase dysfunction.